Geographical and climatic risk factors for COVID-19 in southwest Iran during the 2020–2021 epidemic - Koorosh Nikaein; Zahra Kanannejad; Mohammad Amin Ghatee (PLoS ONE, 2025)
The COVID-19 pandemic has had a devastating impact worldwide, with Iran being one of the hardest-hit countries in the Middle East. Understanding the factors that influence the spread of the virus is crucial for developing effective mitigation strategies. This study aims to investigate the geographical and climatic risk factors associated with COVID-19 incidence in the Kohgiluyeh and Boyer-Ahmad Province of southwest Iran during the 2020−2021 epidemic period. The study involved mapping the residential addresses of 15,585 patients with COVID-19 during 2020–2021. Geographical Information System (GIS) evaluated the effects of geographical and climatic determinants, including temperature, rainfall, humidity, evaporation, elevation, slope, and land cover, on COVID-19 occurrence. The data were analyzed using univariate and multivariate binary logistic regression. In the univariate model, significant climatic factors affecting COVID-19 susceptibility included elevation (p < 0.001, OR=0.617), evaporation (p < 0.001, OR=0.635), dusty days (p < 0.001, OR=1.050), humidity (p = 0.005, OR=1.013), and rainfall (p = 0.032, OR=0.998). Additionally, urban areas (p < 0.001, OR=65), irrigated farms (p < 0.001, OR=5.723), dry farms (p < 0.001, OR=3.101), thin forests (p = 0.009, OR=2.975), and thin rangeland (p = 0.030, OR=2.571) demonstrated the highest impact on the disease distribution. In the multivariate analysis, urban areas (p < 0.001 and OR=47.123), irrigated farms (p < 0.001, OR=4.510), dry farms (p = 0.006, OR=3.002), evaporation (p < 0.001, OR=0.999), and elevation (p < 0.001, OR=0.999) were found to be the main factors related to COVID-19 occurrence. Based on the study results, individuals living in urban areas, irrigated and dry farms, as well as in regions with lower elevation and lower evaporation, have a higher risk of contracting COVID-19.